Reconstructing The Legal Protection Of Indonesian Migrant Workers Facing The Death Penalty (Jinayat) In Saudi Arabia: National And International Legal Perspectives - Ahmad Muchlis; Pujiyono Pujiyono; Nabitatus Sa'adah (Syariah: Jurnal Hukum dan Pemikiran, 2025)
Â  This study examines the reconstruction of the legal protection model for Indonesian migrant workers (PMI) facing the death penalty in Saudi Arabia from both national and international legal perspectives. The research aims to evaluate the effectiveness of existing legal instruments, identify implementation gaps, and propose a comprehensive, human rightsâ€“based model of protection. Employing a normative juridical (doctrinal) method, the study analyzes Indonesiaâ€™s constitutional and statutory framework, international conventions such as the Vienna Convention on Consular Relations (1963), and the structure of Saudi Arabiaâ€™s jinÄyÄt legal system. The findings reveal that although Indonesia possesses a robust national legal framework, weak implementation, inadequate inter-agency coordination, and limited bilateral enforcement mechanisms continue to expose migrant workers to severe human rights risks, particularly due to Saudi Arabiaâ€™s non-compliance with Mandatory Consular Notification (MCN). The study recommends the establishment of binding bilateral agreements, the strengthening of legal diplomacy and attachÃ© functions, and the harmonization of national law with international human rights standards. The implications highlight that migrant worker protection must operate as an integrated systemâ€”covering prevention, legal assistance, and post-trial supportâ€”to effectively realize the stateâ€™s constitutional duty to protect its citizens abroad. Â